Towards the usage of simulation as a tool for the analysis of investment projects - Diego Andrés Carreño Dueñas, Lilia Teresa Bermúdez Correa, (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This work is supported by a literature review on various fields of action, about the simulation technique, it seek to give an overview on the use of process simulation to solve business problems, with the purpose of demonstrating their high potential application, focusing particularly on the subject of the analysis of investment projects.